2022
DOI: 10.3390/ijms23179737
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Transcriptome and Metabolome Reveals the Regulation of Chitooligosaccharide on Drought Tolerance in Sugarcane (Saccharum spp. Hybrid) under Drought Stress

Abstract: Sugarcane (Saccharum spp. hybrid) is an important crop for sugar and biofuels, and often suffers from water shortages during growth. Currently, there is limited knowledge concerning the molecular mechanism involved in sugarcane response to drought stress (DS) and whether chitooligosaccharide could alleviate DS. Here, we carried out a combined transcriptome and metabolome of sugarcane in three different treatment groups: control group (CG), DS group, and DS + chitooligosaccharide group (COS). A total of 12,275 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…2-oxocarboxylic acids connect various amino acid metabolism/ synthesis pathways, including the tricarboxylic acid cycle, and play an important role in plant drought resistance. Yang et al (2022), who examined sugarcane response to drought, reported that 2oxocarboxylic acid metabolism was the most important enrichment pathway. In this study, 2-oxocarboxylic acid metabolism was found to play an essential role in both soybean varieties.…”
Section: Discussionmentioning
confidence: 99%
“…2-oxocarboxylic acids connect various amino acid metabolism/ synthesis pathways, including the tricarboxylic acid cycle, and play an important role in plant drought resistance. Yang et al (2022), who examined sugarcane response to drought, reported that 2oxocarboxylic acid metabolism was the most important enrichment pathway. In this study, 2-oxocarboxylic acid metabolism was found to play an essential role in both soybean varieties.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, based on the DEGs between F172 and GT31 under drought stress, the results of the KEGG pathway analysis showed that starch and sucrose metabolism, and glycolysis/gluconeogenesis were extensively enriched for all comparisons ( Figures 2B, C ). Changes in these two metabolic pathways may be some of the most common responses to drought because these pathways are also significantly enriched for the IACSP97-7065, IACSP94-2094, and ROC22 sugarcane varieties under drought stress ( Contiliani et al., 2022 ; Yang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2018) reported that drought inhibits photosynthesis; further, MAPK cascades modulate plant tolerance to drought ( Bashir et al., 2019 ). Drought can also affect the levels of secondary plant metabolites such as calcium, anthocyanins, flavonoids, phenolic acids, chlorophyll and saponins ( Yu et al., 2020 ; Contiliani et al., 2022 ; Yang et al., 2022 ). Wan et al.…”
Section: Discussionmentioning
confidence: 99%
“…The functions of the DEMs enriched pathways were studied using the Kyoto Encyclopedia of Genes and Genomes (KEGG) database ( https://www.genome.jp/kegg/pathway.html ). When the metabolic pathway p value was less than 0.05, the metabolic pathway was considered statistically significant enrichment [ 18 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…html). When the metabolic pathway p value was less than 0.05, the metabolic pathway was considered statistically significant enrichment [18,21].…”
Section: Metabolite Extraction and Untargeted Metabolomic Analysismentioning
confidence: 99%